Overview and prospect of the history of air pollution control in the United States in the 20th century - Wang, Jie (International Journal of Social Sciences and Public Administration, 2024)
Environmental history, as a comprehensive discipline method and research paradigm, started in the 1970s, and air pollution control is the most important field in environmental governance. After more than 50 years of relevant research and accumulation, scholars at home and abroad have achieved fruitful results in the history of air pollution control in the United States. In terms of the overall study of the history of air pollution in the United States, almost all the stages of American air control in the 20th century have been systematically studied by the academic community. In terms of case studies, cases such as the photochemical smog incident in Los Angeles and California’s advanced air management in California have also been well studied. In terms of the research of relevant laws and precedents, important laws such as the "Clean Air Act" and important concepts such as "bubble" have been systematically studied, and various court cases have been sorted out and compiled. In terms of urban environmental history, the existence of social inequality in society has been valued. However, at the same time, there is room for further research in the air governance process of the United States between the 1940s and 1960s, the Donora smoke event, some detailed rules and standards in the "Clean Air Act", and further research efforts can be made to realize the innovation of transnational and even globalization.